Internal training load: perception of volleyball coaches and athletes - Francine Caetano de Andrade Nogueira; Ruan Alves Nogueira; Danilo Reis Coimbra; Bernardo Miloski; Victor Hugo de Freitas; Maurício Bara Filho (Universidade Federal de Santa Catarina, 2014)
The aim of this study was to evaluate the correspondence between perceived internal load of volleyball players of different positions with perceived internal load planned by the coach, as well as to compare the perceptions of internal training load between different positions in volleyball. The sample was composed of 15 professional volleyball players who were members of a 2012/2013 team in the Brazilian first division league. The athletes answered the Borg CR-10 scale after training, while the coach answered before the training, as was planned for this study. Data analysis was performed Kappa (K), one-way and two-way ANOVA with Tukey post-hoc using the statistical packages SPSS 19.0 and Statistica 8.0. The results indicated that all positions showed good agreement with the perception of the coach and no significant differences in perceptions of internal training load. However, when analysing the percentage of athletes' perceptions of intensity proposed by the coach, it was observed that athletes overestimate the sessions of easy training, while they underestimate the intensity of heavy training. The results indicate that there may be differences between the perceptions of coaches and athletes and reinforce the importance of adopting strategies for monitoring/control of daily training loads.